ANALISIS STRATEGI BERSAING DAN PERPINDAHAN KONSUMEN FRIED CHICKEN DENGAN METODE GAME THEORY DAN MARKOV CHAIN - Pasaribu, Tigor Gabriel; Sari, Rianita Puspa; Krishna Purba, Syafa Fadhilla (BAROMETER, 2023)
Competition strategy needs to be done to retain consumers. With case studies at outlets X fried chicken and Y fried chicken have problems in retaining consumers, so it is necessary to have a strategy for competition and analysis of opportunities for consumer movement. Data collection was carried out using a questionnaire method and literature study. To complete the case studies at X fried chicken and Y fried chicken outlets, the Game Theory method was used to select the optimal strategy to win the competition and the Markov Chain method to analyze opportunities for consumer switching. The results of processing using the game theory method of the two players namely outlets X fried chicken and Y fried chicken have the same value, therefore both players have a pure strategy, where X fried chicken uses a strategy in terms of taste and Y fried chicken uses a strategy in terms of price. With the Markov Chain method, there was a decrease in consumer movement of X fried chicken from period 0 (current period) to period 5 (5th month period) from 89.7% to 37.3% and there was an increase in consumer movement of Y fried chicken from period 0 (current period) to period 5 (5 month period) ranging from 10.3% to 62.7%.